2021
DOI: 10.1186/s40478-021-01281-9
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine 136 phosphorylation of α-synuclein aggregates in the Lewy body dementia brain: involvement of serine 129 phosphorylation by casein kinase 2

Abstract: Serine 129 (S129) phosphorylation of α-synuclein (αSyn) is a central feature of Lewy body (LB) disease pathology. Although the neighboring tyrosine residues Y125, Y133, and Y136 are also phosphorylation sites, little is known regarding potential roles of phosphorylation cross-talk between these sites and its involvement in the pathogenesis of LB disease. Here, we found that αSyn aggregates are predominantly phosphorylated at Y136 in the Lewy body dementia brain, which is mediated by unexpected kinase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…To cover all possible C-terminal tyrosine phosphorylation modifications, we also included the polyclonal aSyn pY133 and pY136 antibodies from Abcam. To the best of our knowledge, these two C-terminal tyrosine phosphorylations have not been explored in post-mortem tissues, with the exception of one recent study (Sano et al, 2021). The specificities of these three Abcam antibodies were validated in hippocampal and cortical aSyn KO neurons by ICC and WB (Supplementary Figure 9A-C; Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To cover all possible C-terminal tyrosine phosphorylation modifications, we also included the polyclonal aSyn pY133 and pY136 antibodies from Abcam. To the best of our knowledge, these two C-terminal tyrosine phosphorylations have not been explored in post-mortem tissues, with the exception of one recent study (Sano et al, 2021). The specificities of these three Abcam antibodies were validated in hippocampal and cortical aSyn KO neurons by ICC and WB (Supplementary Figure 9A-C; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrated aSyn in post-mortem human studies has been previously reported (Duda et al, 2000) but the site-specific N-terminal nitration at Y39 was not investigated due to the lack of an antibody targeting this modification specifically. Similarly, only a handful of studies so far have investigated the N-terminal (Chen et al, 2009; Mahul-Mellier et al, 2014) and C-terminal (Sano et al, 2021) tyrosine phosphorylations. Here we describe the widespread co-presence of these modifications across LB disorders scattered to neurons and glia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the α-synuclein C-terminal tail contains the majority of phosphorylation sites ( Figure 3 ). Phosphorylation of α-synuclein Ser129 is mediated by several kinases such as G-protein-coupled receptor kinases (GRKs) [ 54 , 55 , 56 ], casein kinase II [ 56 , 57 , 58 ], polo-like kinases [ 59 , 60 , 61 ], and leucine-rich repeat kinase 2 (LRRK2) [ 62 , 63 ]. Below, we summarize the α-synuclein phosphorylation kinases and describe the associated pathogenic neurotoxicity.…”
Section: Kinases That Phosphorylate α-Synuclein and Their Association...mentioning
confidence: 99%
“…These data indicate that CK2α can enhance the phosphorylation of pSer129 α-synuclein. In addition, Sano et al found that α-synuclein aggregates are predominantly phosphorylated at Y136 in brains with DLB, which is mediated by the activity of CK2 [ 58 ]. Furthermore, aggregate formation with Ser129 phosphorylation was significantly attenuated by CK2 inhibition, which increased Y136 phosphorylation in cultured neuroblastoma SH-SY5Y cells [ 58 ].…”
Section: Kinases That Phosphorylate α-Synuclein and Their Association...mentioning
confidence: 99%
“…We hypothesized that the presence of multiple PTMs in the C-terminus could significantly influence or mask the detection of pS129-aSyn 1,3,[21][22][23][24] . To test this hypothesis, we systematically assessed, for the first time, the effect of the co-occurrence of pathologyassociated C-terminal PTMs on the detection of pS129-aSyn.…”
Section: Introductionmentioning
confidence: 99%